ANALISIS PERJANJIAN KREDIT SINDIKASI DI PERBANKAN DAN KAITANNYA DENGAN PRINSIP KEHATI-HATIAN - Eka Ermala; Arga Chon Feriandref, Othman Ballan, Mubaraq, Duwi Aryadi (INTELIGENSIA MEDIA, 2025)
This research aims to identify and analyze the arrangements and procedures for applying for Syndicated Credit in Banking and their relationship to the Prudential Principle which is the basis for Principles in Banking. The formulation of the problem that will be discussed in this article is about procedures, requirements and legal rules governing syndicated credit in banking. The type of research is normative law, namely a research method that emphasizes legislation, conceptual law and case law, as well as explaining theories related to the research problem. The research results show that the implementation of Syndicated Credit is related to the rights and obligations of the parties. As long as the parties fulfill these requirements and carry out the agreed agreements and carry out supervision simultaneously, the risk of default will be smaller. Regulations regarding authority, rights and obligations between the Debtor and the Bank in the Syndicated Credit Agreement must be stated clearly in the Syndicated Credit Agreement so that there are no gaps in the norms that could cause problems in the future.